2020
DOI: 10.1111/cobi.13538
|View full text |Cite
|
Sign up to set email alerts
|

Loss and vulnerability of lowland forests in mainland Southeast Asia

Abstract: Despite containing extraordinary levels of biodiversity, lowland (<200 m asl) tropical forests are extremely threatened globally. Southeast Asia is an area of high species richness and endemicity under considerable anthropogenic threat with, unfortunately, scant focus on its lowland forests. We estimated extent of lowland forest loss from 1998 to 2018, including inside protected areas and determined the vulnerability of this remaining forest. Maximum likelihood classification techniques were used to classify L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 61 publications
(110 reference statements)
0
29
1
Order By: Relevance
“…Forest loss and degradation affect many migratory landbirds throughout their distributions in the EAF, particularly at the tropical wintering grounds (Amano and Yamaura, 2007;. Asian tropical lowlands have suffered the highest rates of forest loss globally (Corlett, 2014;Stibig et al, 2014;Namkhan et al, 2021). Extensive deforestation throughout the lowlands of the Greater Sundas is predicted to affect both globally threatened and more common species that winter predominantly in lowland forest (Wells, 2007;.…”
Section: Habitat Loss and Degradationmentioning
confidence: 99%
“…Forest loss and degradation affect many migratory landbirds throughout their distributions in the EAF, particularly at the tropical wintering grounds (Amano and Yamaura, 2007;. Asian tropical lowlands have suffered the highest rates of forest loss globally (Corlett, 2014;Stibig et al, 2014;Namkhan et al, 2021). Extensive deforestation throughout the lowlands of the Greater Sundas is predicted to affect both globally threatened and more common species that winter predominantly in lowland forest (Wells, 2007;.…”
Section: Habitat Loss and Degradationmentioning
confidence: 99%
“…Tropical East Asia supports an estimated 15–25% of global terrestrial biodiversity in only 4% of global land area 8 and many studies have identified this region’s species and ecosystems as particularly threatened 8 11 . Unfortunately, this region, as well as most of the individual countries of which it is comprised, is relatively data-poor, with incomplete species lists, inadequate conservation assessments, and a lack of data on population sizes and trends for threatened species 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Forestry practices in Southeast Asia are gradually improving (Keenan et al 2015, MacDicken et al 2015, but regulations, targets, and effectiveness vary widely, and reduced-impact logging techniques are mainly limited to a few countries in the region (FAO 2011a). Deforestation and fires remain serious problems (Miettinen et al 2011, Wilcove et al 2013, Dong et al 2014, Margono et al 2014, Hansen et al 2020, especially in the lowlands (Namkhan et al 2020), but also with worrying, previously unrecognized increases in higher elevations (Zeng et al 2018). Moreover, forests can become degraded while seemingly remaining intact, due to the limits of resolution of remote sensing (FAO 2011b, Margono et al 2012, Bryan et al 2013, Miettinen et al 2014.…”
Section: Discussionmentioning
confidence: 99%